Severe infections in recipients of cancer immunotherapy: what intensivists need to know. Issue 5 (10th October 2022) - Joseph, Adrien; Lafarge, Antoine; Mabrouki, Asma; Abdel-Nabey, Moustafa; Binois, Yannick; Younan, Romy; Azoulay, Elie
Abstract : Purpose of review: Given the increased number of cancer patients admitted in the ICU and the growing importance of immunotherapy in their therapeutic arsenal, intensivists will be increasingly confronted to patients treated with immunotherapies who will present with complications, infectious and immunologic. Recent findings: Apart from their specific immunologic toxicities, cancer immunotherapy recipients also have specific immune dysfunction and face increased infectious risks that may lead to intensive care unit admission. Summary: Chimeric antigen receptor T-cell therapy is associated with profound immunosuppression and the risks of bacterial, fungal and viral infections vary according to the time since infusion. Immune checkpoint blockers are associated with an overall favorable safety profile but associations of checkpoint blockers and corticosteroids and immunosuppressive drugs prescribed to treat immune-related adverse events are associated with increased risks of bacterial and fungal infections. The T-cell engaging bispecific therapy blinatumomab causes profound B-cell aplasia, hypogammaglobulinemia and neutropenia, but seems to be associated with fewer infectious adverse events compared with standard intensive chemotherapy. Lastly, intravesical administration of Bacillus Calmette-Guérin (BCG) can lead to disseminated BCGitis and severe sepsis requiring a specific antibiotherapy, often associated with corticosteroid treatment.